Learning Management Strategy Based STAD-Model as an Innovation for Quality Development in Islamic Elementary Schools - Novita, Mona; Ningsih, Ayu Arisma; Ahmadi, Mohammad Khan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
This study aims to improve students’ learning interest in Mathematics through the implementation of the Student Teams Achievement Division (STAD) learning model in Grade III of SDN 101/II Muara Bungo. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart spiral model, which was conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The participants were 35 elementary students. Data were collected through observation, interviews, and documentation, and were analyzed qualitatively and quantitatively using descriptive techniques. The findings revealed a significant improvement in students’ learning interest across three indicators—attention, active participation, and positive attitude toward learning activities. The average percentage of learning interest increased from 40.37% in the pre-cycle, to 53.80% in Cycle I, and reached 73.84% in Cycle II. These results indicate that the STAD model successfully created an engaging, collaborative, and student-centered learning environment. The use of “mystery card” learning media during the STAD process also enhanced students’ motivation and engagement. Therefore, the STAD model proved effective in increasing students’ interest in learning Mathematics at the elementary school level.